The diffusion fluxes and sediment activity of phosphorus in the sediment–water interface of Poyang Lake. Issue 4 (1st October 2016) - Yang, Zhiping; Liang, Tao; Li, Kexin; Zhang, Qian; Wang, Lingqing
ABSTRACT: The dissolved reactive phosphorous (DRP) in pore water releases into the water body through the sediment–water interface. The DRP concentrations in the water and sediment of Poyang Lake were determined by high-resolution pore diffusion balance (HR-Peeper) and Zr-oxide diffusive gradients in thin films (Zr-oxide DGT) techniques. The range of the DRP concentrations in the pore water samples of different sampling sites was 30–360 ng/cm 3 . The diffusion fluxes of DRP in the sediment–water interface were calculated based on the DRP concentration gradients. The range of DRP flux in Poyang Lake was 4.78–40.5 ng m −2 d −1 with an average value of 14.7 ng m −2 d −1 . The results showed that the P diffusion flux was higher in the middle of the Poyang Lake than both upstream and downstream of the lake.